Assessment of Wind Energy Potential across Different Köppen Climatic Zones of Nigeria Using RETScreen Expert - Okpala, Chidozie (FUDMA Journal of Sciences, 2026)
The increasing demand for clean and sustainable energy has intensified the need to evaluate Nigeria’s wind energy resources across different climatic regions. This study assessed the wind energy potential of selected stations within Nigeria’s Köppen climatic zones using Weibull statistical modelling and the RETScreen (Renewable Energy Technologies Screen) Expert platform. Weibull shape and scale parameters were estimated to determine Wind Power Density (WPD) and extrapolated hub-height wind characteristics. The computed WPD values were subsequently used in RETScreen simulations to estimate Annual Energy Generation (AEG), Capacity Factor (CF), and Greenhouse Gas (GHG) reduction potential using the Vestas V90. The results revealed significant climatic variability in wind energy potential across Nigeria. Stations located within the northern arid and semi-arid climatic zones (BWh and BSh) generally exhibited stronger wind resources and better turbine performance than stations within the humid southern climatic zones. Baga recorded the highest WPD of 181.8 W/m², corresponding to an AEG of 3220 MWh/year, CF of 18.38%, and GHG reduction potential of 3330 tCO₂/year, indicating moderate suitability for wind power development. In contrast, Aba and Port Harcourt exhibited extremely low wind resource conditions that resulted in non-feasible turbine outputs. The climatic suitability ranking followed the order: BWh > BSh > Aw > Am, confirming northern Nigeria as the most promising region for utility-scale wind energy development. The study demonstrates that integrating Weibull modelling with RETScreen Expert provides a reliable approach for regional wind energy assessment and sustainable energy planning.
Keywords: Wind Energy Potential; Retscreen Expert; Weibull Distribution; Wind Power Density; Köppen Climatic Zones; Capacity Factor